2021
DOI: 10.1111/ajt.16439
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and aging-associated syndromes in lung transplant candidates and recipients

Abstract: Many lung transplant candidates and recipients are older and frailer compared to previous eras. Older patients are at increased risk for pre‐ and posttransplant mortality, but this risk is not explained by numerical age alone. This manuscript represents the product of the American Society of Transplantation (AST) conference on frailty. Experts in the field reviewed the latest published research on assessment of elderly and frail lung transplant candidates. Physical frailty, often defined as slowness, weakness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…26,27 The lack of association between frailty and age as seen in our study demonstrates the independence of these two constructs, fitting with the conceptual framework of frailty as independent from chronologic age. 13 Other studies using different frailty evaluations in lung transplantation have similarly demonstrated a lack of association between frailty and age. 28,29 In our study, frailty was associated with the number of hospital readmissions in the first year, but not LOS in the initial posttransplant hospitalization.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…26,27 The lack of association between frailty and age as seen in our study demonstrates the independence of these two constructs, fitting with the conceptual framework of frailty as independent from chronologic age. 13 Other studies using different frailty evaluations in lung transplantation have similarly demonstrated a lack of association between frailty and age. 28,29 In our study, frailty was associated with the number of hospital readmissions in the first year, but not LOS in the initial posttransplant hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…Frailty is common in older adults but is defined as a state of decreased physiologic reserve independent of age. Studies have found that frailty is linked with worse outcomes, including an increased risk of early post‐transplant mortality using a range of methods for assessing frailty 11,12,13,14,15 . In lung transplant patients, frailty has also been associated with an increase in rehospitalization 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor to consider in assessing cognition is increasing age and normative age-related cognitive changes, which may be of particular concern given the generally aging population in the United States and increasing age of transplant recipients [53,54]. Recent studies have also found that the prevalence of global cognitive impairment and cognitive impairment burden steadily increased with age in kidney transplant populations [55 ▪ ].…”
Section: Clinical Ethical and Cultural Considerations In Assessment A...mentioning
confidence: 99%
“…25 Recent consensus reports have endorsed the development of frailty assessment tools as a future direction of research for transplantation studies. [26][27][28] We hypothesized that the FI could integrate the multiple elements routinely assessed during CF and LT evaluation to quantify risk and that, although LT would improve pulmonary impairment, increased frailty and social/lifestyle vulnerability would negatively impact post-LT outcomes. Our aim was to develop a CF-specific FI to allow risk stratification of CF patients listed for LT and to validate this approach in an independent cohort.…”
Section: Introductionmentioning
confidence: 99%